2019
DOI: 10.3390/pharmaceutics11100501
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Thermosensitive Formulation Based on Polyurethane Hydrogel/Mesoporous Glasses for Sustained Co-Delivery of Functional Ions and Drugs

Abstract: Mini-invasively injectable hydrogels are widely attracting interest as smart tools for the co-delivery of therapeutic agents targeting different aspects of tissue/organ healing (e.g., neo-angiogenesis, inflammation). In this work, copper-substituted bioactive mesoporous glasses (Cu-MBGs) were prepared as nano- and micro-particles and successfully loaded with ibuprofen through an incipient wetness method (loaded ibuprofen approx. 10% w/w). Injectable hybrid formulations were then developed by dispersing ibuprof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 41 publications
3
52
4
Order By: Relevance
“…We have previously reported that [15][16][17] aqueous solutions of the here-studied amphiphilic PEU, containing Poloxamer® 407 as building block, undergo temperature driven sol-to-gel transition by micelle self-assembly. In this work, the effect of plasma treatment on PEU thermosensitivity was studied, by estimating the critical micellar temperature of aqueous solutions of the modified polymer.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…We have previously reported that [15][16][17] aqueous solutions of the here-studied amphiphilic PEU, containing Poloxamer® 407 as building block, undergo temperature driven sol-to-gel transition by micelle self-assembly. In this work, the effect of plasma treatment on PEU thermosensitivity was studied, by estimating the critical micellar temperature of aqueous solutions of the modified polymer.…”
Section: Introductionmentioning
confidence: 92%
“…The P407-based poly(ether urethane) used in this work was synthesized under nitrogen atmosphere in a two step procedure according to the protocol recently published by Boffito, Pontremoli et al [16]. Briefly, P407 was first dissolved in DCE at 20% w/V concentration and equilibrated at 80 • C; then, HDI was added to P407 solution at 2:1 molar ratio.…”
Section: Synthesis Protocolmentioning
confidence: 99%
“…Pontremoli et al (2018) reported the development of hybrid sol-gel systems based on a custom-made poly(ether urethane) (PEU) containing F127 as building block and ion-doped bioactive glasses (MBGs) in the form of nanoparticles or microspheres, demonstrating that the resulting composite formulations allowed a prolonged and sustained release of copper ions over time. Later, the same authors described similar injectable formulations co-releasing copper ions and ibuprofen (Boffito et al, 2019b). Interestingly, they demonstrated that drugs could be released from hybrid formulations with an anomalous mechanism resulting from the existence of a double diffusive barrier (i.e., the hydrogel and the mesoporous framework) the drug molecules must pass through before being released in the surrounding aqueous medium.…”
Section: Introductionmentioning
confidence: 99%
“…The administration of the BMP-2 loaded SD-MBG in particulate form enables versatility in dosing, since different clinical applications certainly require adjustable concentrations, and shaping of the blood clot is equally customizable. The SD-MBG can be injected if contained in a liquid dispersion and the embedding moiety can be exchanged based on the specific requirements, e.g., to a thermo-sensitive hydrogel that solidifies at body temperature [ 30 , 71 ]. However, it should be noted that the composite utilized in this study does not provide mechanical or distinct structural support to guide bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we analyzed mesoporous bioactive glasses, produced in the form of microspheres by aerosol-assisted spray-drying method (SD-MBGs) [ 29 ], as an alternative promising carrier for BMP-2 instead of the currently used ACS. We selected SD-MBGs due to their intrinsic excellent bioactive behavior and related pro-regenerative potential, along with the high exposed surface area and regular nanopores, which allow the storage and the release of active agents, such as drugs [ 30 ] or biomolecules [ 31 ]. Based on previous studies showing the suitability of mesoporous bioactive glass microspheres (MBGs) for sustained drug release [ 32 ], we hypothesized that the SD-MBGs could act as a carrier for BMP-2 that controls and prolongs BMP-2 release without hindering the healing process.…”
Section: Introductionmentioning
confidence: 99%